What should be the object of research with respect to the notion of mathematical proof? - Zakaria Ndemo; David J Mtetwa; Fred Zindi (Intelektual Pustaka Media Utama, 2019)
Despite its central place in the mathematics curriculum the notion mathematical proof has failed to permeate the curriculum at all scholastic levels. While the concept of mathematical proof can serve as a vehicle for mathematical thinking, studies have revealed that students experience serious difficulties with proving that include: not knowing how to begin the proving process, the proclivity to use empirical verifications for tasks that call for axiomatic methods of proving, resorting to rote memorization of uncoordinated fragments of proof facts. While several studies have been conducted with the aim of addressing students’ fragile grasp of mathematical proof the majority of such studies have been based on activities that involve students reflecting and expressing their level of convincement in arguments supplied by the researchers thereby compromising the voice of the informants. Further, research focus has been on the front instead of the back of mathematics. Hence, there is a dearth in research studies into students’ thinking processes around mathematical proof that are grounded in students’ own proof attempts. Therefore current research strides should aim at identifying critical elements of students’ knowledge of the notion of proof that should be informed by students’ actual individual proof construction attempts.